Compatibility of tailings–nonwoven geotextile under stress and the effect of sand filter. Issue 3 (3rd June 2020) - Liu, S.; Wang, Y.; Feng, D.
Abstract : Geotextiles have been widely used in engineering drainage. The clogging of geotextile filters used in fine tailings dams often occurs owing to complex environmental conditions. To better understand the influence of stress and the hydraulic gradient ( i ) on the hydraulic compatibility of fine tailings–nonwoven geotextile filter, a series of gradient ratio (GR) tests were performed in this study. To reduce the physical clogging and enhance the drainage capability of nonwoven geotextiles, a layer of sand filter was placed between the tailings and the nonwoven geotextiles. The effects of the sand filter were explored by GR tests and the following beneficial conclusions were drawn: Compaction induced by normal stress increased the interlocking between tailings particles. Consequently, the internal stability of the tailings increased, which lowered the clogging potential and volume of drainage of the system. The value of i (1-20) had only a slight effect on the clogging potential and permeability coefficient of the tailings, especially in case of high normal stress. The sand filter prevented the formation of filter cake at the soil–geotextile boundary, and increased volume of drainage of the system. This reduced the clogging potential and enhanced the drainage capability of the system.